Ação da torta de mamona e de algodão sobre o nematoide de cisto das cactáceas (Cactodera cacti) - Santos Filho, Rogério Jucá dos (2024)
Plant nematodes include pathogens capable of parasitizing plants and causing serious damage, such as nematodes of the Heteroderidae family, of which the cyst-forming genera Heterodera and Cactodera stand out. The species C. cacti has been reported to affect cacti in different countries since 1932. In Ceará, Brazil, it was recorded in mandacaru in 2018. In studies conducted at the UFC Plant Health Sector, red pitaya (Hylocereus costaricensis) is a potential host for C. cacti, indicating that, under field conditions, the pathogen can cause production limitations for the crop. Therefore, aiming to investigate the effect of castor oilseed and cottonseed cakes, with known nematicidal action, on the C. cacti population, three experiments were carried out with this pathogen. The first test, carried out in the laboratory, consisted of evaluating the following concentrations of castor oilseed cake: 0; 0.5; 1; 2, and 4 g per liter of distilled water, which were filtered after 24 hours of immersion. The filtrates were distributed in Petri dishes, which contained 1 mL of suspension containing 50 C. cacti eggs, which were obtained from cysts extracted by the CS method, for extraction of soil cysts, and Coolen and D'Herde for extraction of root cysts. The plates were observed daily for 20 days under an optical microscope to observe the hatching of second-stage juveniles (J2). In vitro tests with cottonseed cake were not viable. The second test was conducted in a greenhouse with pitaya seedlings inoculated with the nematode. Initially, 10 cysts of the pathogen were deposited in plastic bags containing 1 kilogram of autoclaved substrate (sand, manure, vermicompost, and carnauba bagasse in a ratio of 2:1:1:1). Six concentrations of castor bean cake and cottonseed cake (0; 0.5; 1; 2; 4 and 5 g) were also added to the bags, and the cakes were standardized with the substrate. Then, the mixture (substrate, cysts, and cake) was poured into 2-kg pots and irrigated daily. Two weeks later, pitaya seedlings were transplanted into these pots after 25 days of rooting. After 45 days, the effect of the cakes on the nematode was evaluated considering the number of cysts present in the roots. The seedlings, duly identified, were removed from the pots and taken to the laboratory to extract the pathogen from the roots using the same methods used for cyst extraction in the in vitro experiment. The nematode suspension was taken to a stereomicroscope for counting of J3, J4, females, and cysts. The in vitro and in vivo tests were conducted in a completely randomized design (CRD) with 5 replicates. The results of the in vitro test with the 5 castor bean cake treatments demonstrated that, in general, there was a reduction in the hatching rate of juveniles, being greater in the treatment with the highest cake dose (4.0 g), in which an average of 6.8 juveniles hatched per plate, corresponding to 13.6% hatching. In the other treatments, the values were 20.8%, 34.0%, and 40.0% hatching, according to the reduction in the castor bean cake dose (2; 1, and 0.5 g). In the control (water), the hatching rate was 57.2%. In the second experiment, carried out in a greenhouse, it was observed that the average number of cysts present in the roots of the control pitayas (dose 0) was 94.4. In the treatments with castor bean cake, there was a reduction in the number of cysts/root system of 48.7%; 56.1%; 58.9%; 97.2%, and 98.9%, respectively, about the control, for the doses of 0.5; 1; 2; 4 and 5 g. In the third trial, an average number of 96.2 cysts were observed in the roots of the control plants (dose 0). For the treatments with cottonseed cake, there was a decrease in the number of cysts of 32.2%; 49.5%; 58.8%; 92.9%, and 97.1% for the doses of 0.5; 1; 2; 4, and 5 g, respectively, in comparison with the control. The in vivo results demonstrated that castor bean and cottonseed cake at doses of 4.0 and 5.0 g significantly reduced the number of pathogen cysts, suggesting that they can be used in the management of C. cacti. In general, no phytotoxic effect of the cakes on the cactus seedlings was observed, considering the uniform green appearance of the cladodes, similar to that of the controls.